Valor nutritivo de dietas e desempenho bioeconômico de Ovinos alimentados à base de silagem de capim elefante contendo torta de algodão - Dias, Elyane Cristina Borges (2012)
This study was conducted in order to verify the nutritional value, digestibility and bio-economic performance of sheep fed by a particular diet which had different levels of inclusion, (0, 7, 14, 21%) of cottonseed meal (CM) in elephant grass (EG) silage. We studied 20 sheep (½ Morada Nova x ½ with no specific breed) males, intact, with initial bodyweight of 17.5 ± 0.5 kg and approximately 6 months old. The experimental design was completely randomized with four treatments and five replications. The inclusion of cottonseed meal in elephant grass silage has shown to be efficient to increase the dry matter content of the silage. An increased linear effect was observed (P<0.5) with the inclusion of cottonseed meal in the contents of dry matter (DM), crude protein (CP), ether extract (EE), lignin (LIG), ammonia nitrogen and pH. For the contents of mineral residue (MR), neutral detergent fiber (NDF), neutral detergent fiber transformed into ash and protein (NDFap), there was a quadratic effect (P<0.5). No effects were observed on the non-fiber carbohydrate values. There was no significant difference across the diets for the consumption of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), ether extract (EE), total carbohydrates (TC), non-fiber carbohydrates (NFC) (g/animal/day; % BW and g/metabolic). as far as the used diet is concerned. Regarding apparent digestibility (%) of DM, OM, CP, NDF, EE and TCHO, there was a decrease in DMS and BMD (P<0.5) and an increase of CM levels and a decrease in the DPB with the addition of CM to EG silage. In addition, for DEE, there was a decrease of 0.05 percentage points for every 1% of CM added to elephant grass silage. The DNDF, decreased 0.54 percentage points for every1% of CM. We also evaluated the consumption of NDT (% DM), CED, CEM, which showed no difference between the treatments. For nitrogen balance (NB) of the silages, there was a decreasing linear effect (P<0.5) with the inclusion of cottonseed meal. In regard to the performance, we evaluated the final weight (kg), total weight gain (TWG), average daily gain (ADG) and the number of days that the lambs needed to gain 12 kg (D12). By analyzing the TWG variable (kg), we perceived that there was no difference between the diets (P>0.5). Still, the lambs that were fed with the diet that used 21% cottonseed meal obtained the highest final weight, total weight gain and average daily gain (g/d), as well as a lesser number of days to gain 12 kg. The analyses of the different systems were based on simulations using two hundred lambs per batch. The cost of each feed and the consumption of dry matter enabled us to analyze technical, zootechnical and economic indicators. It was estimated that R$3.20/kg BW is the sales price of the animals, for all diets. This helps to know which of the systems (0, 7, 14, 21% of cottonseed meal in silage elephant grass) is more profitable. Thus, the variety of economic and investment analysis performed can lead us to conclude that the systems only become profitable when the lambs and sales prices are R$ 7, 95/kg BW, R$7, 67/kg BW, R$ 7, 16/kg BW and 8,63/kg BW respectively.